Synthesis of octahedral Pt–Ni–Ir yolk–shell nanoparticles and their catalysis in oxygen reduction and methanol oxidization under both acidic and alkaline conditions. Issue 48 (29th November 2019) - Yang, Tao; Wang, Yihui; Wei, Wenxian; Ding, Xinran; He, Maoshuai; Yu, Tingting; Zhao, Hong; Zhang, Dongen
Abstract : A Pt–Ni–Ir yolk–shell catalyst was synthesized using facile processes and displayed superior catalytic activity for oxygen reduction and methanol oxidization. Abstract : Fuel cells are expected to be one of the most promising alternatives to the increasingly scarce fossil fuels, and Pt is the most commonly used catalyst for anodic and cathodic electrochemical reactions. To realize large-scale commercialization, it is most urgent to improve the efficiency of Pt and reduce the cost. Here, we synthesized an octahedral Pt–Ni–Ir yolk–shell catalyst through stepwise co-deposition (SCD), surface-limited Pt deposition (SLPD) and Ni-coordinating etching (NCE) processes. Experimental studies showed that the catalytic activities of the as-prepared trimetal yolk–shell catalyst were several times higher than that of the commercial Pt/C towards oxygen reduction and methanol oxidization under both acidic and alkaline conditions. This work may be extended to designing other multimetallic functional materials with complex hierarchical nanostructures, which is conducive to greatly enhancing the performance.